Immersion of Sargassum binderi Seaweed in River Water Flow to Lower Salt Content before Use as Feed for Laying Hens - Dewi, Yelsi listiana; Yuniza, Ahadiyah; Nuraini; Sayuti, Kesuma; Mahata , Maria Endo (International Journal of Poultry Science, 2017)
Background and Objective: In certain coastal areas of Indonesia, Sargassum binderi drifts to the shore because of ocean waves and because people do not use it, becomes useless waste. This seaweed could potentially be used as feed for laying hens because certain bioactive compounds in seaweed, such as alginate, fucoidan, fucoxanthin and poly-unsaturated fatty acids (PUFA), are useful for poultry health. High salt content is a problem with using Sargassum binderi as poultry feed because it causes diarrhea and death in poultry. Therefore, the salt content of Sargassum binderi should be reduced before it is fed to poultry. The purpose of this study was to reduce the salt content of Sargassum binderi for use as feed for laying hens. Materials and Methods: The experiment was arranged in a completely randomized design with Sargassum binderi immersed in flowing river water for durations of 0, 3, 5, 7, 9, 11, 13, 15, 19, 21 and 23 h, each treatment was repeated 3 times. The measured variables were salt, crude protein, total dry matter, organic matter and ash. Results: The results showed that the different immersion durations of Sargassum binderi in flowing river water significantly affected (p<0.05) the reduction of salt, total dry matter and ash content and also significantly affected (p<0.05) the increase in organic matter and crude protein. Conclusion: The immersion of Sargassum binderi in flowing river water for 15 h was the best treatment to lower salt, total dry matter and ash and to increase the organic matter and crude protein content.